Eternal Youth: Gymnasts, Ageing and Body Narratives across Sport, Media and Post– Career Trajectories - Caputo, Ylenia (Mediascapes journal, 2025)
Gymnastics is a discipline that offers the possibility to explore the complex relationship between body, ageing and gender. Professional gymnasts, who reach the peak of their physical performance during adolescence, appear to undergo an anomalous alteration of the ageing process, shaped by both extrinsic elements (intense physical effort, strict dietary regimes, the use of pharmacological substances) and intrinsic ones (the natural biological metamorphosis). As is well known, the developmental phase, with the changes it entails – first and foremost the onset of menstruation – affects the athletes’ physical performance. Their young bodies are thus prematurely perceived, experienced and managed as if they were “old bodies”, generating a paradox that translates into concrete attempts to delay such ageing, through practices that, in fact, reverse the process and confine gymnasts within a sort of “perpetual youth”, with all the associated physical, biological, psychological, and even social implications. In exploring this phenomenon, reference will be made to the representations and narratives of gymnasts in the media, with a specific focus on the docu-series Ginnaste – Vite Parallele (MTV, 2011–2016) and the fiction The Gymnasts (Corpo libero, Rai 2, 2023). Furthermore, exemplary figures in the discipline will be taken into account, such as Carlotta Ferlito for Italy and Simone Biles for the United States, who, as public and cross-media personalities, contribute to the redefinition of the female body, ageing and heroism, in the sporting context and beyond.